Die Limoniiden-Abbildungen Meigen’s. (Versuch einer Deutung der Limoniiden-Arten Meigen’s auf der Grundlage seiner Farbtafeln im Naturhistorischen Museum zu Paris). - Mendl, Hans (Contributions to Entomology = Beiträge zur Entomologie, 1979)
On the basis of Meigen’s coloured plates found in the Museum of Natural History in Paris, the pressent paper makes an attemt to explain the genera of Limoniidae according to Meigen, a number of which had not been clarified so far Limoniidae. Nomenclatural Acts transversa (Meigen, 1804) (Dactylolabis), comb. n. hitherto Limnobia transversa flavescens Meigen, 1804 (Erioptera), syn. n. of Erioptera (Erioptera) gemina Tjeder, 1967 montana Meigen, 1818 (Erioptera), nom. obl. now a synonym of Ormosia staegeriana Alexander, 1953 taenionota Meigen, 1818 (Erioptera), syn. n. of Erioptera (Erioptera) lutea Meigen, 1818 angustipennis Meigen, 1818 (Limnobia), syn. n. of Limnobia pictipennis (Meigen, 1804) annulus Meigen, 1804 (Limnobia), syn. n. of Metalimnobia quadrimaculata (Linnaeus, 1761) binotata Meigen, 1838 (Limnobia), syn. n. of Pedicia (Crunobia) littoralis (Meigen, 1804) collaris Meigen, 1838 (Limnobia), nom. obl. now Gonomyia (Protogonomyia) alboscutellata (von Roser, 1840) fulvescens Meigen, 1818 (Limnobia), syn. n. of Phylidorea (Euphylidorea) lineola (Meigen, 1804) humilis Meigen, 1830 (Limnobia), nom. obl. now Austrolimnophila (Austrolimnophila) unica Osten Sacken, 1869 iridea Meigen, 1804 (Limnobia), nom. nudum now Dicranomyia (Dicranomyia) modesta (Meigen, 1818) leucophaea Meigen, 1818 (Limnobia), syn. n. of Neolimnomyia (Brachylimnophila) nemoralis (Meigen, 1818) lutea Meigen, 1804 (Limnobia), nom. obl.; syn. n. of Dicranomyia (Dicranomyia) chorea (Meigen, 1818) marmorata Meigen, 1804 (Limnobia), syn. n. of Eloeophila maculata (Meigen, 1804) nigrina Meigen, 1830 (Limnobia), nom. obl. now Phylodorea (Euphylodorea) meigeni (Verrall, 1887) nitidicollis Meigen, 1818 (Limnobia), nom. obl. now Paradelphomyia (Oxyrhiza) senilis (Haliday, 1833) nova Meigen, 1830 (Limnobia), syn. n. of Dicranomyia (Dicranomyia) modesta (Meigen, 1818) pacifica Meigen, 1804 (Limnobia), nom. nudum now Limonia pabulina (Meigen, 1818) pallida Meigen, 1804 (Limnobia), nom. nudum now Pedicia (Crunobia) straminea (Meigen, 1838) picta Meigen, 1804 (Limnobia), syn. n. of Epiphragma ocellaris (Linnaeus, 1761) plebeia Meigen, 1818 (Limnobia), nom. obl. now Neolimnomyia (Neolimnomyia) filata (Walker, 1848) pratorum Meigen, 1830 (Limnobia), syn. n. of Phylidorea (Euphylidorea) phaeostigma (Schummel, 1829) pulla Meigen, 1830 (Limnobia), syn. n. of Triogma trisulcata (Schummel, 1829) quadra Meigen, 1838 (Limnobia), syn. n. of Dicranomyia (Dicranomyia) chorea (Meigen, 1818) ruralis Meigen, 1838 (Limnobia), syn. n. of Pilaria discicollis (Meigen, 1818) sexpunctata Meigen, 1804 (Limnobia), nom. obl. now Limnobia nigropunctata var. nigrescens Lackschewitz, 1928 simplex Meigen, 1830 (Limnobia), syn. n. of Dicranomyia (Dicranomyia) modesta (Meigen, 1818) usta Meigen, 1804 (Limnobia), nom. nudum now Dactylolabis sexmaculata (Macquart, 1846) xanthoptera Meigen, 1804 (Limnobia), syn. n. of Metalimnobia bifasciata (Schrank, 1781) pictipennis (Meigen, 1804) (Limnophila (Limnophila)), comb. n. hitherto Limnobia pictipennis Anisomera Meigen, 1818 (Limoniidae), syn. n. of Hexatoma Latreille, 1809 Glochina Meigen, 1830 (Limoniidae), syn. n. of Dicranomyia Stephens, 1829 Limnobia Meigen, 1818 (Limoniidae), syn. n. of Limonia Meigen, 1803 Rhamphidia Meigen, 1830 (Limoniidae), syn. n. of Helius Lepeletier & Serville, 1828 nigricollis (Meigen, 1804) (Phylidorea (Phylidorea)), comb. n. hitherto Limnobia nigricollis inornata Meigen, 1830 (Rhamphidia), syn. n. of Helius longirostris (Meigen, 1818) punctipennis Meigen, 1804 (Symplecta), syn. n. of Symplecta hybrida (Meigen, 1804)